2020
DOI: 10.1038/s41398-020-01018-7
|View full text |Cite
|
Sign up to set email alerts
|

Immune response and endocytosis pathways are associated with the resilience against Alzheimer’s disease

Abstract: Developing Alzheimer’s disease (AD) is influenced by multiple genetic variants that are involved in five major AD-pathways. Per individual, these pathways may differentially contribute to the modification of the AD-risk. The pathways involved in the resilience against AD have thus far been poorly addressed. Here, we investigated to what extent each molecular mechanism associates with (i) the increased risk of AD and (ii) the resilience against AD until extreme old age, by comparing pathway-specific polygenic r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 68 publications
2
43
0
Order By: Relevance
“…Recently, increased parental life span was associated with a lower PRS of low-density lipoprotein cholesterol levels, systolic blood pressure, and body mass index ( 15 ). We previously showed that cognitively healthy centenarians have a significantly lower PRS of Alzheimer’s disease (AD) compared to population controls ( 43 ). The overlap between the variants that contribute to the AD PRS and our best longevity PRS is limited: Apart from APOE variants, the longevity-associated variant rs9665907 is in LD with the known AD variant rs11218343 (in/near SORL1 , R 2 = 0.39) ( 44 ), and the variant rs6558008 is in low LD with the known AD variant rs9331896 (in/near CLU , R 2 = 0.05) ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increased parental life span was associated with a lower PRS of low-density lipoprotein cholesterol levels, systolic blood pressure, and body mass index ( 15 ). We previously showed that cognitively healthy centenarians have a significantly lower PRS of Alzheimer’s disease (AD) compared to population controls ( 43 ). The overlap between the variants that contribute to the AD PRS and our best longevity PRS is limited: Apart from APOE variants, the longevity-associated variant rs9665907 is in LD with the known AD variant rs11218343 (in/near SORL1 , R 2 = 0.39) ( 44 ), and the variant rs6558008 is in low LD with the known AD variant rs9331896 (in/near CLU , R 2 = 0.05) ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, groups sizes were also relatively small, but the centenarians had a relatively high level of cognitive health, which might have contributed to an increased effect size of AD-associated genetic variants in our comparison. 16,17…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this this version posted February 4, 2021. ; https://doi.org/10.1101/2021.02.02.21250991 doi: medRxiv preprint high level of cognitive health, which might have contributed to an increased effect size of AD-associated genetic variants in our comparison. 16,17…”
Section: Ad-associated Variants and Their Effect On Healthy Agingmentioning
confidence: 99%
See 2 more Smart Citations